Spesies Kupu-Kupu (Rhopalocera) Di Tanjung Balai Karimun Kabupaten Karimun, Kepulauan Riau - Nofri Sea Mega Sutra; - Dahelmi; Siti Salmah (Jurnal Biologi Universitas Andalas, 2012)
A study on butterflies (Rhopalocera) at Tanjung Balai Karimun was conducted from December 2011 to April 2012. The purposes of this study is to know the butterfly species at Tanjung Balai Karimun, Karimun Regency, Riau Archipelago. Butterflies were collected by insect net, cylindrical gauze and baited trap. A total of 42 species of butterflies that belonging 55 subspecies, 32 genera ang eigth families was collected. They were belong to Acraeidae, Amathusiidae, Danaidae, Lycaenidae, Nymphalidae, Papilionidae, Pieridae, and Satyridae. The highest number of species was found in family of Nymphalidae (15 species, 21 subspecies, 12 genera), and the lowest number of species was found in Acraeidae (Acraea violae Fabricius) and Amathusiidae (two genus, two spesies dan three subspesies). Five species of butterflies in this study have not been found in previous studies from Sumatra. They were Zeuxidia amethystus Butler (Amathusiidae), Euploea crameri C & R. Felder (Danaidae), Arhopala avatha de Niceville (Lycaenidae) and Euthalia mahadeva Fabricius, Lebadea martha Fruhstorfer (Nymphalidae).Keywords: rhopalocera, species, Tanjung Balai Karimun, Riau Archipelago